Thrombotic microangiopathy without renal involvement: two novel mutations in complement‐regulator genes. (1st February 2016) - Peyvandi, F.; Rossio, R.; Ferrari, B.; Lotta, L. A.; Pontiggia, S.; Ghiringhelli Borsa, N.; Pizzuti, M.; Donadelli, R.; Piras, R.; Cugno, M.; Noris, M.
Abstract : Essentials The differential diagnosis among thrombotic microangiopathies (TMAs) is challenging. We studied a case of TMA with neurologic symptoms, no renal impairment and normal ADAMTS‐13 levels. Two novel mutations in complement factor I and thrombomodulin genes were identified. Complement‐regulator genes can be involved in TMAs with normal ADAMTS‐13 regardless of renal damage. Summary: Background: Thrombotic microangiopathies (TMAs) often represent a challenge for clinicians, because clinical, laboratory, and even genetic features are not always sufficient to distinguish among different TMAs. Objectives: The aim of this study was to investigate the pathogenetic mechanisms underlying an acute case of TMA with features of both thrombotic thrombocytopenic purpura (TTP) and atypical hemolytic uremic syndrome (aHUS). Patients/Methods: We report the case of a 49‐year‐old woman who developed an acute TMA with neurologic involvement and no renal impairment. ADAMTS‐13, von Willebrand factor, and complement‐system biochemical characterization was performed on acute phase samples. Exome sequencing and direct Sanger sequencing of previously aHUS‐associated genes were performed. The functional consequences of the thrombomodulin ( THBD ) mutation were investigated by in vitro expression studies. Results: Despite a clinical diagnosis of TTP, the patient had normal ADAMTS‐13 levels and increased VWF antigen levels with ultra‐large von Willebrand factor multimers. C3, C4, and complement factors H and I (CFI) were normal. Molecular analysis confirmed two novel heterozygous mutations in CFI (c.805G>A, p.G269S) and THBD (c.1103C>T, p.P368L), and in vitro expression studies showed a reduction in the generation of activated thrombin‐activatable fibrinolysis inhibitor (TAFIa) caused by mutated THBD . This proinflammatory condition, associated with the p.G269S mutation in CFI, probably leads to a complement‐mediated endothelial activation, with a relevant prothrombotic potential in case of transient environmental triggers. Conclusions: This study identified the first case of acute TMA without renal involvement but with neurological damage carrying two novel mutations in complement‐regulator genes, highlighting the possible role of the complement system as a common pathogenetic mechanism in TMAs.